Adhesions, infl ammatory response and foreign body giant cells infi ltration of the topical hemostats TachoSil®, Hemopatch™ and Veriset™ - An Animal Study - Line Schiøtt Nissen; Jacob Hunter; Henrik Daa Schrøder; Kenneth Rütz; Peter Bollen (Journal of Surgery and Surgical Research - Peertechz Publications, 2017)
Background: When liver bleeding cannot be controlled by conventional methods, a topical hemostatic patch can be applied during surgery. In recent years new hemostats have become available. The aim of this study was to investigate the degree of adhesion and inflammation for three topical hemostatic patches, TachoSil®, Hemopatch™ and Veriset™. Methods: In 60 adult male Sprague Dawley rats liver two lesions were induced with a scalpel. Each rat was treated with two of the three patches tested. After 1, 2 and 3 months the animals were euthanized and macroscopic evaluation of adhesions and histological assessment of inflammation and macrophage infiltration were performed. Results: A significant higher (p<0.05) occurrence of foreign body giant cells (FBGCs) was found in Hemopatch™ and Veriset™, whereas both had a lower degree of inflammatory and macrophage infiltration compared to TachoSil®. No differences in the occurrence of adhesions were found. Conclusion: Our study found evidence for difference in inflammation and formation of foreign body giant cells for the three hemostatic patches.